Evolving Synergy Between Synthetic and Biotic Elements in Conjugated Polyelectrolyte/Bacteria Composite Improves Charge Transport and Mechanical Properties - Samantha R. McCuskey; Glenn Quek; Ricardo Javier Vázquez; Binu Kundukad; Muhammad Hafiz Bin Ismail; Solange E. Astorga; Yan Jiang; Guillermo C. Bazan (Advanced Science)
Abstract gLiving materials can achieve unprecedented function by combining synthetic materials with the wide range of cellular functions. Of interest are situations where the critical properties of individual abiotic and biotic elements improve via their combination. For example, integrating electroactive bacteria into conjugated polyelectrolyte (CPE) hydrogels increases biocurrent production. One observes more efficient electrical charge transport within the CPE matrix in the presence of Shewanella oneidensis MR‐1 and more current per cell is extracted, compared to traditional biofilms. Here, the origin of these synergistic effects are examined. Transcriptomics reveals that genes in S. oneidensis MR‐1 related to bacteriophages and energy metabolism are upregulated in the composite material. Fluorescent staining and rheological measurements before and after enzymatic treatment identified the importance of extracellular biomaterials in increasing matrix cohesion. The synergy between CPE and S. oneidensis MR‐1 thus arises from initially unanticipated changes in matrix composition and bacteria adaption within the synthetic environment.